Preparation of solar photo-thermal conversion material with strong near-infrared light absorption and application of solar photo-thermal conversion material in degradation of organic pollutants

By increasing the load concentration of ultra-thin iron base oxide material, prepare the FE3O4 nanometer absorbed near infrared light, and load it to the PVDF film. Combined with PMS advanced oxidation technology, it solves The problem of low -quality and low -heating materials has achieved efficient solar utilization and organic pollutant degradation.

CN119349693AActive Publication Date: 2025-01-24HEFEI UNIV OF TECH

Patent Information

Application Number
CN202411699713.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-24
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing SMD-PMS technology introduces a large amount of sulfates and toxic organic by-products when treating actual wastewater, and lacks efficient photothermal materials to maximize the use of solar energy to generate heat.

Method used

By increasing the surface carrier concentration of ultra-thin iron-based oxide materials, Fe3O4 nanosheets with near-infrared light intensity absorption are prepared and loaded onto the PVDF membrane to form a Fe3O4/PVDF composite distillation membrane. Combined with PMS advanced oxidation technology, For sewage purification.

Benefits of technology

The efficient sunlight conversion is realized, the ability of solar utilization and organic pollutants has been improved, and the introduction of sulfate and toxic byxinates is avoided. It has a high amount of floral flux, which is suitable for actual sewage purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349693A_ABST
    Figure CN119349693A_ABST
Patent Text Reader

Abstract

The invention discloses preparation of a solar photo-thermal conversion material with strong near-infrared light absorption and application of the solar photo-thermal conversion material in degradation of organic pollutants. The preparation method comprises the following steps: firstly, preparing an oxidation precursor FeOOH, and calcining in a nitrogen atmosphere to generate Fe3O4 nanosheets; and loading the Fe3O4 nanosheets on the surface of the PVDF membrane through a mixed binder to obtain the Fe3O4 / PVDF composite distillation membrane. The Fe3O4 nanosheets have strong absorption in visible light and near-infrared light regions, so that the prepared Fe3O4 / PVDF composite distillation membrane has strong photo-thermal performance and high membrane fresh water flux, and efficient removal of organic pollutants in water and recovery of fresh water can be realized by combining the sunlight-driven Fe3O4 / PVDF composite distillation membrane with PMS to treat sewage. The method is expected to be applied to actual sewage purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical fields of metal nanomaterial synthesis, advanced oxidation technology and solar membrane distillation, and specifically relates to the preparation of a solar thermal conversion material with strong near-infrared light absorption and its application in the degradation of organic pollutants. Background Art

[0002] As the impact of human activities on the environment continues to increase, the global available freshwater resources are becoming increasingly scarce. Emerging pollutants in water bodies, such as endocrine disruptors and trace organic pollutants such as pharmaceuticals and personal care products, cause water pollution problems that are becoming increasingly serious, seriously threatening human health. In order to achieve freshwater resource regeneration, the development of efficient water purification technology has become a focus of scientific research. The permonosulfate (PMS) advanced oxidation technology based on sulfate radicals can oxidize pollutants into water and carbon dioxide to achieve the removal of refractory organic pollutants, making it expected to become an efficient treatment method for emerging organic pollutants in water bodies. However, when the PMS advanced oxidation technology treats actual sewage (such as secondary effluent from sewage treatment plants, high-salt wastewater from petrochemicals, etc.), a large amount of sulfate will be introduced into the sewage, and toxic organic byproducts may also be introduced. In recent years, solar membrane distillation (SMD), driven by green energy solar energy, has achieved seawater desalination and has attracted widespread research attention. SMD can not only effectively intercept sulfate and organic byproducts, but also the heat generated by ultraviolet rays and photothermal conversion in SMD can activate PMS for the degradation of organic pollutants. Therefore, it is of great significance to design the combined technology of SMD and PMS advanced oxidation technology (SMD-PMS) for wastewater purification.

[0003] At present, SMD research lacks efficient photothermal materials to maximize the use of solar energy to generate heat. Infrared light accounts for about 50% of the sunlight spectrum. Compared with visible light and ultraviolet light, the vibration frequency of infrared light is closer to the frequency of material molecules, making it easier to cause molecular resonance in the material. In addition, the alternating electromagnetic field accompanying its propagation will cause the molecules of the material to alternately polarize, resulting in a significant thermal effect of the reciprocating relaxation motion of a large number of molecules, thereby achieving efficient solar thermal conversion. Therefore, designing and synthesizing solar thermal conversion materials with strong near-infrared light absorption to improve the utilization rate of solar energy is of great research significance to SMD-PMS. Summary of the invention

[0004] In view of the deficiencies of the above-mentioned prior art, the present invention provides a preparation of a solar thermal conversion material with strong absorption of near-infrared light and its application in the degradation of organic pollutants. The present invention can achieve strong absorption of near-infrared light by increasing the surface carrier concentration of ultra-thin iron-based oxide materials to achieve efficient solar thermal conversion, and is used in SMD-PMS to simultaneously improve the utilization rate of solar energy and the degradation ability of organic pollutants. By comparing the solar thermal conversion ability of Fe3O4 nanoparticles prepared by conventional methods, it is shown that the Fe3O4 nanosheets prepared by the present invention have good solar thermal conversion ability. The prepared Fe3O4 nanosheets are loaded onto a PVDF membrane, and the sewage containing organic pollutants is removed by irradiating the Fe3O4 / PVDF composite distillation membrane in combination with PMS. At the same time, the Fe3O4 / PVDF composite distillation membrane has a high membrane freshwater flux and can achieve considerable freshwater recovery, which is expected to be applied to actual sewage purification.

[0005] The preparation method of the solar thermal conversion material with strong near-infrared light absorption of the present invention comprises the following steps: firstly preparing an oxidized precursor FeOOH, calcining it in a nitrogen atmosphere to generate Fe3O4 nanosheets; then loading the Fe3O4 nanosheets onto the surface of a PVDF membrane by mixing a binder, and obtaining a Fe3O4 / PVDF composite distillation membrane. Step 1: Preparation of FeOOH precursor Dissolve CTAB in pure water, adjust the pH of the solution, add FeSO4·7H2O and stir until completely dissolved, add NaBH4, stir and react for 12 h, collect the product and wash it with water and ethanol until neutral, and vacuum dry it for 12 h to obtain FeOOH precursor.

[0006] Step 2: Preparation of Fe3O4 nanosheets The FeOOH precursor was placed in a tube furnace, heated to 400 °C under a N2 atmosphere and kept at this temperature for 4 h, then cooled to room temperature to obtain black Fe3O4 nanosheets.

[0007] Step 3: Preparation of Fe3O4 / PVDF composite distillation membrane Fe3O4 is uniformly dispersed in a mixed solution of Nafion and ethanol to obtain a Fe3O4 dispersion, which is then coated on the surface of a PVDF membrane to form a uniform coating to obtain a Fe3O4 / PVDF composite distillation membrane.

[0008] At the same time, the present invention also prepared Fe3O4 nanoparticles as a comparison: 2.70g FeCl3·6H2O and 2.79g FeSO4·7H2O were dissolved in 25mL sulfuric acid solution and magnetically stirred at 80°C for 15 min; then 250mL of 4 mol / L NaOH solution was dripped into the mixture through a peristaltic pump within 15 min, and stirring was continued for 75 min in an inert nitrogen environment. The product was collected and washed with water and ethanol, and vacuum dried for 12 h to obtain black Fe3O4 nanoparticles.

[0009] In step 1, 0.728 g of CTAB was added, which was dissolved in 200 mL of pure water and the pH value of the solution was adjusted to 3; then 0.167 g of FeSO4.7H2O was added, stirred until completely dissolved, and then 0.12 g of NaBH4 was added.

[0010] In step 2, the heating rate is controlled so that the tube furnace is heated from room temperature to 400°C in ten minutes and maintained at 400°C for 4 hours.

[0011] In step 3, the ratio of Nafion to ethanol was 1:6, and 70 mg of Fe3O4 nanosheets were added after uniform mixing.

[0012] In step 3, each PVDF membrane was cut into a rectangle with a size of 4 cm × 2 cm, and 4.5 mL of Fe3O4 nanosheet dispersion was used to evenly coat three PVDF membranes.

[0013] The Fe3O4 / PVDF composite distillation membrane prepared by the invention is used in activating peroxymonosulfate to degrade organic pollutants.

[0014] Specifically, PMS is added to wastewater containing organic pollutants, and the wastewater is passed through the Fe3O4 / PVDF membrane surface. Under light conditions, the PMS is activated to produce active substances to degrade the organic pollutants in the wastewater. The degraded wastewater is extracted at the same interval, centrifuged and filtered, and the remaining content of organic pollutants is detected by HPLC.

[0015] The concentration of PMS in the system was 15 mM / L.

[0016] The illumination source is a xenon lamp with a light intensity of 100 mW / cm 2 ; The degradation time is 1 h.

[0017] The system temperature was controlled at 30 °C, and the flow rate in the hot material zone was 20 mL / min.

[0018] The organic pollutant is bisphenol A (BPA).

[0019] In HPLC detection, the sample was processed before detection by adding 1 mL of the reaction mixture to 1 mL of methanol for quenching, centrifuging at 8000 rpm for 2 min, and filtering the supernatant with a 0.22 μm membrane. The chromatographic column used for HPLC detection was Shim-pack GIST C18 (150×4.6 mm, 5 μm). The ratio of water to methanol in the mobile phase was 20:80 (V / V), and the flow rate was 1 mL / min. BPA was detected using a UV detector with a detection wavelength of 276 nm.

[0020] Iron-based oxide nanomaterials are widely used in PMS activation due to their rich content and environmental friendliness. However, traditional iron-based oxide nanomaterials have low carrier concentrations and cannot achieve strong near-infrared absorption. The present invention can achieve strong absorption of near-infrared light by increasing the surface carrier concentration of ultra-thin iron-based oxide materials to achieve efficient solar light-to-heat conversion, and is used in SMD-PMS to simultaneously improve the utilization rate of solar energy and the degradation capacity of organic pollutants.

[0021] The beneficial effects of the present invention are embodied in: The prepared Fe3O4 nanosheets are loaded onto a PVDF membrane, and the Fe3O4 / PVDF composite distillation membrane is illuminated to activate PMS to produce active substances to remove organic pollutants in sewage. In order to maximize the degradation performance of this method, the loading amount of Fe3O4 on each Fe3O4 / PVDF membrane is 3 mg / cm 2 , the concentration of PMS was 0.1 g / L, which achieved efficient degradation of organic pollutants and improved the utilization rate of catalyst Fe3O4. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the X-ray diffraction pattern (XRD) of FeOOH in Example 1. Figure 1 It can be seen that the prepared material is consistent with the FeOOH PDF#81-0462 card, indicating that the prepared material is FeOOH.

[0023] Figure 2 is the XRD of Fe3O4 nanosheets in Example 1. Figure 2 It can be seen that the calcined material is consistent with Fe3O4PDF#79-0417, indicating that the obtained material is Fe3O4.

[0024] Figure 3 is the XRD of Fe3O4 nanoparticles in Example 2. Figure 3 It can be seen that the prepared material is consistent with Fe3O4PDF#99-0073, indicating that the prepared material is Fe3O4.

[0025] Figure 4 is the XRD of Fe3O4 nanosheet A in Example 3. Figure 4 It can be seen that the prepared material is consistent with Fe3O4PDF#72-2303, indicating that the prepared material is Fe3O4.

[0026] Figure 5 is the XRD of Fe3O4 nanosheet B in Example 3. Figure 5 It can be seen that the prepared material is consistent with Fe3O4PDF#99-0073, indicating that the prepared material is Fe3O4.

[0027] Figure 6 is a transmission electron microscope image of FeOOH in Example 1. Figure 6 It can be seen that the prepared FeOOH has a flake-like structure.

[0028] Figure 7 TEM image of Fe3O4 nanosheets in Example 1. Figure 7 It can be seen that the Fe3O4 nanosheets obtained after calcination are a broken sheet-like structure.

[0029] Figure 8 FIG. 2 is a transmission electron microscope image of Fe3O4 nanoparticles in Example 2. Figure 8 It can be seen that the prepared Fe3O4 nanoparticles are in the form of long strips.

[0030] Fig. 9 TEM image of Fe3O4 nanosheet A in Example 3. Fig. 9 It can be seen that the Fe3O4 nanosheets A prepared by other methods exhibit a regular rectangular sheet structure.

[0031] Fig.10 TEM image of Fe3O4 nanosheet B in Example 3. Fig.10 It can be seen that the Fe3O4 nanosheet B prepared by other methods is a sheet-like structure.

[0032] Fig.11 The Fe3O4 nanosheet / PVDF membrane in Example 4 was exposed to a light intensity of 100 mW / cm 2 The temperature changes at 2-min intervals under the irradiation of a xenon lamp. Fig.11 It can be seen that the temperature of Fe3O4 nanosheets / PVDF membrane can reach up to 114.3℃ under illumination for 6 min.

[0033] Fig.12 The Fe3O4 nanosheet A / PVDF film in Example 4 was exposed to a light intensity of 100 mW / cm 2 The temperature changes at 2-min intervals under the irradiation of a xenon lamp. Fig.12It can be seen that the temperature of Fe3O4 nanosheet A / PVDF membrane can reach up to 50.4℃ under illumination for 6 min.

[0034] Fig.13 The Fe3O4 nanosheet B / PVDF membrane in Example 4 was exposed to a light intensity of 100 mW / cm 2 The temperature changes at 2-min intervals under the irradiation of a xenon lamp. Fig.13 It can be seen that the temperature of Fe3O4 nanosheet B / PVDF membrane can reach up to 64.9℃ under illumination for 6 min.

[0035] Fig.14 The Fe3O4 nanoparticles / PVDF membrane in Example 4 was exposed to a light intensity of 100 mW / cm 2 The temperature changes at 2-min intervals under the irradiation of a xenon lamp. Fig.14 It can be seen that the Fe3O4 nanoparticles / PVDF membrane can reach a maximum of 70℃ under illumination for 6 min.

[0036] Fig.15 The ultraviolet-near infrared light absorption spectrum of Fe3O4 nanosheets and Fe3O4 nanoparticles, Fe3O4 nanosheets A and Fe3O4 nanosheets B in Examples 1, 2 and 3. Fig.15 It can be seen that the Fe3O4 nanosheets prepared by calcining FeOOH as a precursor have good absorption in the visible and near-infrared regions.

[0037] Fig.16 is the bandwidth calculated based on the absorbance using the Tauc plot method. Fig.16 It can be seen that the bandgap (Eg) of the Fe3O4 nanosheet semiconductor prepared by calcining FeOOH as a precursor is 1.20 eV, which has stronger absorption of near-infrared and visible light and better photothermal conversion performance. The Eg of Fe3O4 nanoparticles is 1.46 eV, and the Eg of other Fe3O4 nanosheets is 1.58 eV and 2.08 eV. These materials mainly absorb visible light and have weak absorption of near-infrared light, which reduces the overall energy capture.

[0038] Fig.17 The UV-NIR absorption spectrum of Fe3O4 nanosheet / PVDF membrane and blank PVDF membrane in Example 3. Fig.17 It can be seen that the PVDF membrane loaded with Fe3O4 nanosheets greatly improves the absorption of light.

[0039] Fig.18 In Examples 4 and 6, different Fe3O4 / PVDF membranes were used to activate PMS to degrade BPA under light conditions. Fig.18It can be seen that Fe3O4 nanosheets / PVDF membrane activated PMS can degrade BPA faster.

[0040] Fig.19 The removal rate of BPA by using Fe3O4 nanosheets / PVDF membrane and Fe3O4 nanoparticles / PVDF membrane to activate PMS degradation in Examples 4, 5, and 6 under light and dark conditions, respectively. Fig.19 It can be seen that light helps to enhance the activation of Fe3O4 nanosheets / PVDF membrane to degrade BPA by PMS.

[0041] Fig. 20 The effect of different concentrations of PMS on the degradation efficiency of BPA in Example 7, [BPA] = 10 mg / L, 100 mW / cm 2 , flow rate 20 mL / min. Fig. 20 It can be seen that the degradation effect gradually increases with the increase of PMS concentration.

[0042] Fig.21 The effect of different flow rates in the hot material zone on the BPA degradation efficiency in Example 8. Fig.21 It can be seen that the degradation effect is best when the flow rate is 40 mL / min and 60 mL / min.

[0043] Fig. 22 is the change of membrane water flux under illumination in Example 5. Fig. 22 It can be seen that the membrane flux increases with the increase of the loading amount.

[0044] Fig.23 This is a flow chart of Example 5. DETAILED DESCRIPTION

[0045] In order to make the above-mentioned purpose of the present invention more obvious and understandable, the specific implementation methods of the present invention are further described in detail below in combination with specific embodiments and drawings, but the protection scope of the present invention is not limited to the following embodiments.

[0046] The present invention loads the prepared Fe3O4 nanosheets onto a PVDF membrane, and activates PMS by irradiating the Fe3O4 nanosheet / PVDF composite distillation membrane to generate active substances to remove organic pollutants in sewage. The specific method is: Hexadecyltrimethylammonium bromide (CTAB) was dissolved in pure water to adjust the pH value, and then FeSO4·7H2O and NaBH4 were added and stirred. After washing and vacuum drying, Fe3O4 nanosheets were calcined at 400℃ to obtain Fe3O4 nanosheets. The nanosheets were mixed with Nafion ethanol and evenly applied to PVDF membrane to obtain Fe3O4 / PVDF composite distillation membrane. The Fe3O4 / PVDF composite distillation membrane was irradiated with a xenon lamp to simulate sunlight, and PMS was added to the wastewater to degrade BPA in the wastewater and simultaneously realize fresh water recovery.

[0047] Example 1: Synthesis of Fe3O4 Nanosheets CTAB (728 mg) was dissolved in 200 mL of deionized water and placed in a 250 mL beaker. To inhibit the hydrolysis of FeSO4·7H2O, the pH of the solution was adjusted to 3. FeSO4·7H2O (167 mg) was added to the flask and stirred. After complete dissolution, NaBH4 (120 mg) was added to obtain a black solution. The obtained black solution was exposed to air and stirred at room temperature for 12 h. The product was collected by centrifugation, washed with water and ethanol several times, and finally dried under vacuum at 60 °C to obtain yellow solid FeOOH. The dried FeOOH was ground into powder and placed in a tube furnace. The temperature was raised to 400 °C in a N2 atmosphere for ten minutes and kept at 400 °C for 4 h. Finally, it was taken out after cooling. The obtained Fe3O4 catalyst was characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD).

[0048] Example 2: Synthesis of Fe3O4 nanoparticles with different morphologies FeCl3·6H2O (2.70 g) and FeSO4·7H2O (2.79 g) were dissolved in a conical flask containing sulfuric acid solution (25 mL). The mixed solution was magnetically stirred at 80 °C for 15 min. Then 250 mL of 4 mol / L NaOH solution was dripped into the mixture by a peristaltic pump within 15 min. After the dripping was completed, stirring continued for 75 min. The entire preparation process was carried out in an inert nitrogen environment. When the mixture was cooled to room temperature, the magnetic separation of the synthesized Fe3O4 was completed using a strong magnet. Fe3O4 was washed several times with water and ethanol under neutral pH conditions. Finally, the washed Fe3O4 was dried in a vacuum oven at 40 °C for 12 h.

[0049] Example 3: Synthesis of Fe3O4 nanosheets with different morphologies Prepare 0.025 mol / L potassium ferricyanide aqueous solution, then add 0.0375 mol / L polyvinyl pyrrolidone K30, 0.0625 mol / L sodium hydroxide and 2.25 mol / L ammonia water, stir and dissolve. Put the mixed solution into a hydrothermal reactor and react at 140°C for 12 hours. After the reaction, wash with deionized water and centrifuge for 3-5 times. The obtained product is vacuum dried at 60°C for 12 hours to obtain Fe3O4 nanosheets A.

[0050] 2.3353 g of FeSO4·7H2O and 120 mL of deionized water were fully mixed, 0.64 g of NaOH reagent was added into 80 ml of deionized water, and stirred thoroughly to make it completely dissolved. Then, 6.89 g of sodium acetate was added into the stirred strong alkaline aqueous solution. While treating the mixed solution with an ultrasonic processor, the FeSO4·7H2O aqueous solution was added dropwise into the mixed solution. After the addition was completed, the ultrasonic reaction was continued for 1 hour to obtain a suspension. The ultrasonic power was controlled at 80 W and the frequency was 25 kHz. The solid phase in the suspension was filtered out with filter paper, washed four times with distilled water and anhydrous ethanol respectively, and dried in vacuo at 60°C to obtain Fe3O4 nanosheets B.

[0051] Example 4: Preparation of Fe3O4 / PVDF membrane Take 0.5 mL of Nafion solution and 3 mL of ethanol solution, mix Nafion and ethanol at a ratio of 1:6, add 70 mg of Fe3O4 powder, and mix evenly by ultrasonic. Cut the PVDF membrane into a rectangle of 4 cm × 2 cm, use a pipette to take 1.5 mL of the mixed solution and drop it on the cut PVDF membrane to make it adhere evenly, and then dry it to obtain the Fe3O4 / PVDF membrane.

[0052] Example 5: Fe3O4 nanosheets / PVDF membrane activated PMS to degrade BPA under dark conditions The concentration of BPA was 10 mg / L, and the loading amount of Fe3O4 nanosheets on the membrane was 3 mg / cm 2 , the PMS concentration was 15 mM / L, and the flow rate in the hot zone was 20 mL / min. Every 20 min, 1 mL of the solution was taken into a test tube containing 1 mL of methanol. The concentration of BPA before and after degradation was detected by liquid phase.

[0053] As the reaction proceeded, it was found that the degradation effect of Fe3O4 nanosheets / PVDF membrane on BPA was very poor under dark conditions, and the introduction of light was considered to improve the degradation ability of BPA.

[0054] Example 6: Xenon lamp simulates sunlight to illuminate Fe3O4 nanosheets / PVDF membrane to activate PMS and degrade BPA The concentration of BPA was 10 mg / L, and the loading amount of Fe3O4 nanosheets on the membrane was 3 mg / cm 2 , PMS concentration was 15 mM / L, and the flow rate in the hot zone was 20 mL / min. Xenon lamp (100 mW / cm 2 ), and 1 mL of the solution was taken into a test tube containing 1 mL of methanol every 20 min. The concentration of BPA before and after degradation was detected by liquid chromatography.

[0055] Example 7: Fe3O4 nanoparticles / PVDF membrane made of Fe3O4 nanoparticles activated PMS to degrade BPA by irradiating Fe3O4 nanoparticles with xenon lamp simulating sunlight The concentration of BPA was 10 mg / L, and the loading amount of Fe3O4 nanoparticles on the membrane was 3 mg / cm 2 The PMS concentration was 15 mM / L and the flow rate in the hot zone was 20 mL / min. The xenon lamp (100 mW / cm 2 ), 1 mL of the solution was taken into a test tube containing 1 mL of methanol every 20 min. The concentration of BPA before and after degradation was detected by liquid chromatography.

[0056] As the reaction proceeded, it was found that the Fe3O4 nanoparticles / PVDF membrane made of Fe3O4 nanoparticles was far less effective in degrading BPA within 120 min than the Fe3O4 nanosheets / PVDF membrane made of Fe3O4 nanosheets, indicating that Fe3O4 nanosheets have a better activation effect than other forms of Fe3O4.

[0057] Example 8: Xenon lamp simulated sunlight irradiation Fe3O4 nanosheets / PVDF membrane activation of different concentrations of PMS to degrade BPA The concentration of BPA was 10 mg / L, and the loading amount of Fe3O4 nanosheets on the membrane was 3 mg / cm 2 The PMS dosage was changed (1 mM, 3 mM, 5 mM, 15 mM), and the flow rate in the hot material zone was 20 mL / min. The xenon lamp was used for irradiation (100 mW / cm 2 ), and 1 mL of the solution was taken into a test tube containing 1 mL of methanol every 20 min. The concentration of BPA before and after degradation was detected by liquid chromatography.

[0058] When other conditions remain constant, the removal rate of BPA gradually increases with the increase of PMS concentration.

[0059] Example 9: Xenon lamp simulated sunlight irradiation of Fe3O4 nanosheets / PVDF membrane to activate PMS and degrade BPA under different flow rates in the hot material zone The concentration of BPA was 10 mg / L, and the loading amount of Fe3O4 nanosheets on the membrane was 3 mg / cm 2, the PMS concentration was 15 mM / L, and the flow rate in the hot material zone was changed (20 mL / min, 40 mL / min, 60 mL / min). Xenon lamp was used for irradiation (100 mW / cm 2 ), and 1 mL of the solution was taken into a test tube containing 1 mL of methanol every 20 min. The concentration of BPA before and after degradation was detected by liquid chromatography.

[0060] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a solar thermal conversion material with strong near-infrared light absorption, characterized in that: First, the oxidative precursor FeOOH is prepared and calcined in a nitrogen atmosphere to generate Fe3O4 nanosheets; then the Fe3O4 nanosheets are loaded onto the surface of the PVDF membrane through a mixed binder to obtain a Fe3O4 / PVDF composite distillation membrane.

2. The preparation method according to claim 1, characterized in that The steps include: Step 1: Preparation of FeOOH precursor Dissolve CTAB in pure water, adjust the pH of the solution, add FeSO4·7H2O and stir until completely dissolved, add NaBH4, stir and react for 12 h, collect the product and wash it with water and ethanol until neutral, and vacuum dry it for 12 h to obtain FeOOH precursor; Step 2: Preparation of Fe3O4 nanosheets The FeOOH precursor was placed in a tube furnace, calcined under a N2 atmosphere, and cooled to room temperature to obtain black Fe3O4 nanosheets; Step 3: Preparation of Fe3O4 / PVDF composite distillation membrane Fe3O4 is uniformly dispersed in a mixed solution of Nafion and ethanol to obtain a Fe3O4 dispersion, which is then coated on the surface of a PVDF membrane to form a uniform coating to obtain a Fe3O4 / PVDF composite distillation membrane.

3. The preparation method according to claim 2, characterized in that: In step 1, 0.728 g of CTAB was added and dissolved in 200 mL of pure water, and the pH value of the solution was adjusted to 3; then 0.167 g of FeSO4 was added . 7H2O, stir until completely dissolved and then add 0.12 g NaBH4.

4. The preparation method according to claim 2, characterized in that: In step 2, the heating rate is controlled so that the tube furnace is heated from room temperature to 400°C in ten minutes and maintained at 400°C for 4 hours.

5. The preparation method according to claim 2, characterized in that: In step 3, the ratio of Nafion to ethanol was 1:6, and 70 mg of Fe3O4 nanosheets were added after uniform mixing.

6. The preparation method according to claim 2, characterized in that: The loading amount of Fe3O4 on the Fe3O4 / PVDF composite distillation membrane is 3 mg / cm 2 .

7. Use of the Fe3O4 / PVDF composite distillation membrane prepared according to any one of the preparation methods of claims 1 to 6 in activating peroxymonosulfate to degrade organic pollutants.

8. The use according to claim 7, characterized in that: PMS is added to sewage containing organic pollutants, and the sewage is passed through the Fe3O4 / PVDF membrane surface. Under light conditions, PMS is activated to produce active substances to degrade the organic pollutants in the sewage.

9. The use according to claim 7 or 8, characterized in that: The organic pollutant is bisphenol A.

10. The use according to claim 8, characterized in that: The system temperature was controlled at 30°C, and the flow rate in the hot material zone was 20-60 mL / min.

Citation Information

Patent Citations

  • Preparation method and application of two-dimensional iron oxide nanosheet catalyst

    CN110560062A

  • Preparation method of SnO2 / Fe3O4 composite nano catalyst

    CN114160151A

  • Modified FeOOH / PVDF molecularly imprinted composite membrane as well as preparation method and application thereof

    CN117643869A

  • Method for catalytic degradation of dye wastewater by photocatalysis cooperating with Fenton-like reaction

    CN118754292A

  • Method for preparing targeted catalytic membrane based on surface molecular imprinting nanometer material and application of targeted catalytic membrane

    CN118767916A

Cited By

  • M (2-x-y-z) Zn (2-x-y-z) NxYbyTmzO3 nano photo-thermal material and preparation and application thereof

    CN119823758A